The Influence of Information Technology and The Use of Social Media on Employee Performance at Diskominfo-SP in Utara Luwu District - Amedia, Amedia; Basir, Adil; Syamsuddin, Sofyan (International Journal of Management Science and Information Technology, 2024)
This research aims to evaluate the impact of Technology and the Use of Social Media on the Performance of North Luwu Regency Diskominfo-SP Employees. The research method used is quantitative correlation analysis using SMART PLS 4 with 67 employees as a sample. The research results show that Technology has a positive and significant influence on Employee Performance, with an original sample value of 0.329 and a T statistic of 2.755, at a significance level of <0.5. Likewise, the use of social media also has a positive and significant influence on employee performance, with an original sample value of 0.519 and a T statistic of 3.930, at a significance level of <0.5. The influence of the Technology and Social Media variables on employee performance was measured using the R Square test, which showed 59.2%, while the rest is unknown because it was not included in this research.